Japan : Financial Sector Assessment Program-Technical Note-Regulation and Supervision of Securities. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Japan in the areas of regulation and supervision of securities firms. The supervision of the two major Japanese securities groups and the Japanese subsidiaries of global banking groups deserves special attention, given the domestic and cross-border interconnectedness of these firms. The authorities should continue to ensure that the supervisory teams for the major Japanese groups have access to sufficient number of experienced staff. It is also important to continue to enhance the existing international cooperation in the supervision of Japanese firms' overseas operations and foreign-owned firms' activities in Japan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet